1980
DOI: 10.1084/jem.151.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Feedback suppression of the immune response in vitro. I. Activity of antigen-stimulated B cells.

Abstract: Powerful and often complex regulatory mechanisms that maintain homeostasis are a sine qua non of all carefully studied physiologic activities. Thus, it is not surprising that the immune system has evolved a sophisticated regulatory apparatus for preventing excessive responses to antigenic stimulation. The specific mechanisms so far described include (a) classical antibody feedback which is believed to operate by interference with cellular recognition of antigenic determinants (1, 2) and (b) development of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The realization that B cells have regulatory capacity was initially demonstrated in response to sheep red blood cells and was associated first with regulatory antibody production and later linked to interactions with T cells (Stockinger et al, 1979; Zubler et al, 1980). Subsequent studies in mice and humans have demonstrated that B lymphocytes can regulate immune responses through antibody-dependent mechanisms as well as via direct cell–cell interactions and regulatory cytokine production (Klinker and Lundy, 2012).…”
Section: Systemic Immune Regulation Stimulated By Chronic Schistosomementioning
confidence: 99%
“…The realization that B cells have regulatory capacity was initially demonstrated in response to sheep red blood cells and was associated first with regulatory antibody production and later linked to interactions with T cells (Stockinger et al, 1979; Zubler et al, 1980). Subsequent studies in mice and humans have demonstrated that B lymphocytes can regulate immune responses through antibody-dependent mechanisms as well as via direct cell–cell interactions and regulatory cytokine production (Klinker and Lundy, 2012).…”
Section: Systemic Immune Regulation Stimulated By Chronic Schistosomementioning
confidence: 99%
“…B cells with the capacity to regulate T cell function were originally described by Shimamura et al (6971) and independently by Zubler et al (72, 73) over 30 years ago. In a system of high dose (4 × 10^9) SRBC into C57BL/6 mice, Shimamura et al (71) reported that splenic B cells were able to induce antigen-specific suppressor T cells that subsequently inhibited B cells responses.…”
Section: B Cells As Mediators Of Tolerancementioning
confidence: 99%
“…Recently, immune B cells have been re ported to help in the regulation of the humoral im mune response and contact sensitivity [5][6][7][19][20][21][22][23]. For those experimental systems, it seemed that the suppressor activities of immune B cells were mediated via antibodies, and thus that possibly the idiotypeantiidiotype network was involved.…”
Section: Discussionmentioning
confidence: 99%